Assessment of honey production in Cross River State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
Honey production plays significant roles in socio-economic and environmental development; supplying a significant portion of domestic food and generating income for sustainable livelihood. There is limited information on honey production in Cross River State, Nigeria. This study therefore examines the socio-economic characteristics of honey producers, five-year trends in honey production, and the cost of honey production in Cross River State, Nigeria. Systematic and purposive sampling techniques were used to sample respondents from the area. Beekeepers and hunters were interviewed using a semi-structured questionnaire. Ten Key Informant Interviews and 3 Focus Group Discussions were carried out to verify and enhance the information. Data were analyzed using descriptive (mean, percent and standard deviation) and inferential statistics (ANOVA). The findings revealed that most honey producers are male (96.7% beekeepers, 100% bee-hunters), married (84.7% beekeepers, 93.2% bee-hunters), and have a relatively high level of education (32.6% post-secondary education among beekeepers). The five-year trend shows an increase in honey production among beekeepers (from 192.1 kg to 234.5 kg) and a decline among bee-hunters (from 10.1 kg to 7.5 kg), with beekeepers consistently producing higher quantities of honey. The mean unit price indicates that honey production contributes to the income of individuals in the study area (28.2% of income), with an annual mean income from honey production of ₦113,536.8. Thus, training and empowerment programs should be implemented to support beekeepers, particularly women, while introducing sustainable beekeeping practices and modern technologies to improve efficiency, reduce costs, and increase income for beekeepers, to meet the growing demand for honey.
Keywords: Apiculture; Beehives; Beekeeping; Honey; Sustainable